2018
DOI: 10.1152/jn.00502.2018
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular cerebellar evoked potentials in humans and their modulation during optokinetic stimulation

Abstract: We recorded evoked potentials (EPs) from over the posterior fossa and in parallel ocular vestibular evoked myogenic potentials (OVEMPs) during visuo-vestibular stimulation in a sample of 7 male and 11 female human subjects. In 9 of the 18 subjects we were able to record EPs reliably in the form of an early biphasic positive-negative wave with latencies ~12 and 17 ms ipsilateral to head acceleration direction (P12-N17) and a slightly later, contralateral, biphasic positive-negative wave with latencies ~19 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Several components with peak latencies between 10 and 20 ms appear to reflect parallel spreading of vestibular information to the cerebellum ( 41 , 108 , 110 , 115 , 120 , 149 ) and to several cortical regions, including the precentral sulcus, the precuneus, and cuneus, as well as several frontal areas ( 108 , 113 , 133 ). The exact origin and differentiation of these potentials remain to be clarified, and their cerebellar and cortical generators need to be disentangled from myogenic contributions ( 41 , 108 , 115 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several components with peak latencies between 10 and 20 ms appear to reflect parallel spreading of vestibular information to the cerebellum ( 41 , 108 , 110 , 115 , 120 , 149 ) and to several cortical regions, including the precentral sulcus, the precuneus, and cuneus, as well as several frontal areas ( 108 , 113 , 133 ). The exact origin and differentiation of these potentials remain to be clarified, and their cerebellar and cortical generators need to be disentangled from myogenic contributions ( 41 , 108 , 115 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the literature shows that short, middle and late VestEPs have been found to originate from various cortical areas at similar or close latencies, such as both frontal and occipital activations at 10 ms, or later at 80 ms, for example. The studies available to date suggest that VestEPs with latencies between 10 and 20 ms may have a cerebellar origin ( 41 , 108 , 110 , 115 , 120 , 149 , 150 ), and/or a cerebral origin with several generators in the precentral sulcus ( 108 ) or the precuneus and cuneus ( 113 ) for the n15. Vestibular-evoked potentials with latencies from 20 to 30 ms have been associated to activity in the bilateral anterior insula and posterior operculum ( 111 ) while components with latencies from 40 to 50 ms have been associated with a mid-cingulate source with contributions of the bilateral superior temporal cortex ( 42 , 110 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations